Altered Profile of Fecal Microbiota in Newly Diagnosed Systemic Lupus Erythematosus Egyptian Patients - Gerges, Marian A. (Int J Microbiol, 2021)
BACKGROUND: Dysbiosis of gut microbiota could promote autoimmune disorders including systemic lupus erythematosus (SLE). Clarifying this point would be of great importance in understanding the pathogenesis and hence the development of new strategies for SLE treatment. AIM: This study aimed to determine the fecal microbiota profile in newly diagnosed SLE patients compared to healthy subjects and to investigate the correlation of this profile with disease activity. METHODS: Newly diagnosed SLE patients who fulfilled at least four of the American College of Rheumatology (ACR) criteria were enrolled during the study period. Patients with lupus were matched to healthy subjects. SLE activity was evaluated using the Systemic Lupus Disease Activity Index (SLEDAI-2K). Fresh fecal samples were collected from each subject. Genomic DNA was extracted from fecal samples. Quantitative real-time PCR was applied for quantitation of Firmicutes phylum, Bacteroidetes phylum, and Lactobacillus genus in comparison to the total fecal microbiota. Results of patients' samples were compared to those of healthy subjects and were correlated to patients' SLEDAI-2K score. RESULTS: Twenty SLE patients' samples were compared with 20 control samples. There was a significant alteration in SLE patients' gut microbiota. A significantly lower (p ≤ 0.001) Firmicutes/Bacteroidetes (F/B) ratio in SLE patients (mean ratio: 0.66%) compared to healthy subjects (mean ratio: 1.79%) was found. Lactobacillus showed a significant decrease in SLE patients (p=0.006) in comparison to healthy controls. An inverse significant correlation between SLEDAI-2K scores for disease activity and F/B ratio (r = −0.451; p=0.04) was found. However, an inverse nonsignificant correlation between SLEDAI-2K scores for disease activity and Lactobacillus (r = −0.155; p=0.51) was detected. CONCLUSION: Compared to healthy controls, recently diagnosed SLE Egyptian patients have an altered fecal microbiota profile with significant lowering of both F/B ratio and Lactobacillus abundance, which is weakly correlated with disease activity.